The Role of Trust in Mediating Short-Form Video Ads on Purchase Intention - Denny Sucipto; Kurniawati; Renny Risqiani (Majapahit Journal of Islamic Finance and Management, 2026)
This research explores how characteristics of short video advertisements influence consumer purchasing intent among TikTok users in Indonesia, with trust serving as a mediating factor. The study considers various content features, including informativeness, credibility, consistency, electronic word-of-mouth (eWOM), and appeal. As short-video content gains popularity, marketers are increasingly interested in identifying which elements most effectively foster trust and drive buying decisions. A quantitative approach was employed, involving questionnaires distributed to active TikTok users who had encountered short video ads and had prior online purchase experience. The data were analyzed using Structural Equation Modeling (SEM) in AMOS to assess the relationships between variables and examine trust's mediating role.